View Single Post
May8-08, 02:03 PM
P: 53
1. The problem statement, all variables and given/known data
If g is differentiable and g(x+y)=g(x)(g(y) find g(0) and show g'(x)=g'(0)g(x)

3. The attempt at a solution
I solved g(0)=1


I got as far as

g'(x)=\lim_{\substack{x\rightarrow 0}}g(x) \frac{g(h)-1}{h}

but now I am stuck.

Thank you in advance
Phys.Org News Partner Science news on
Scientists discover RNA modifications in some unexpected places
Scientists discover tropical tree microbiome in Panama
'Squid skin' metamaterials project yields vivid color display